Design IoT-Based Monitoring and Water Control System for Temperature, Humidity, and Ammonia Gas Detection in Chicken Coops Using Blynk - Agung Mumahad Toha; Deri Bahtiar; Iksal Rachman; Yayan Mulyana (Universitas Insan Cendekia Mandiri, 2026)
The poultry industry represents a high-potential sector, yet it currently faces critical challenges in maintaining stable temperature, humidity, and air quality (ammonia gas), which directly impact poultry health, as well as inefficiencies in manual water resource management. This research aims to design and implement an Internet of Things (IoT)-based system for monitoring environmental parameters and controlling water supply using the Blynk platform. The research methodology employed an experimental research and development (R&D) approach, encompassing hardware design (ESP8266, DHT22, MQ135), software development via Arduino IDE, and field testing conducted over five days with periodic data collection at four-hour intervals. The results indicate that the system successfully monitored daily average temperatures ranging from 29.2°C to 30°C (ideal for ±3-week-old broiler chickens), humidity levels between 79% and 81.4%, and real-time ammonia gas concentrations of 17.2–20.1 ppm. Furthermore, the water pump control mechanism, managed through the Blynk application via a relay module, proved effective in precisely meeting hydration requirements, supplying 83.6 ml every four hours for a population of five chickens. Final evaluations demonstrate that the system operates stably and accurately, enhancing the operational efficiency of modern and responsive poultry farming, although its performance remains highly dependent on stable internet connectivity.